PEMAHAMAN PEMUSTAKA PDII-LIPI TENTANG HAK CIPTA - Tupan, Tupan; Nani Rahayu, R.; Rahartri, Rahartri; Mardiana, Mardiana (BACA: Jurnal Dokumentasi dan Informasi, 2009)
This study focuses on how library users of Centre for Scientific Documentation and Information understanding about copyright law. Data was collected by using questionnaires, and collected data were statically analyzed. The respondent consist of 65 students and 46 government official were chosen as respondents. Parameters which were chosen for measuring the understanding of copyright law were how far respondents understand about the law as general; understand about the creations, and then how far they know about the infringement, according to copyright law no. 19/2002. It concludes that generally students less understood about copyright law compared to the government officials, and referring to the students, the understanding of the female student about the law were higher than male students.